2014
DOI: 10.1097/aco.0000000000000041
|View full text |Cite
|
Sign up to set email alerts
|

Applying ‘Patient Blood Management’ in the trauma center

Abstract: PURPOSE OF REVIEW: The purpose of this review is to highlight the use of tranexamic acid, point-of-care testing, algorithm-based treatment of trauma-associated coagulopathy with factor concentrates to reduce blood loss and transfusion requirements in order to improve outcome. In addition, the management of patients on new oral anticoagulants, drugs with renewed interest and the tolerance of relatively low hemoglobin levels in the context of trauma will be discussed. RECENT FINDINGS: Early administration of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 67 publications
(29 reference statements)
0
18
0
1
Order By: Relevance
“…Theusinger et al [25] have demonstrated that blood management concepts to trauma patients are feasible and efficacious and Khan et al [26] have demonstrated that the implementation of haemorrhage protocols may be associated with improved blood product use and patient outcomes in trauma-haemorrhage. The survey by Hoyt et al [16] has similarly reported the frequent use of massive transfusion protocols though a huge heterogeneity was revealed by this survey with respect to the rationale of the treatment algorithm in use.…”
Section: Discussionmentioning
confidence: 99%
“…Theusinger et al [25] have demonstrated that blood management concepts to trauma patients are feasible and efficacious and Khan et al [26] have demonstrated that the implementation of haemorrhage protocols may be associated with improved blood product use and patient outcomes in trauma-haemorrhage. The survey by Hoyt et al [16] has similarly reported the frequent use of massive transfusion protocols though a huge heterogeneity was revealed by this survey with respect to the rationale of the treatment algorithm in use.…”
Section: Discussionmentioning
confidence: 99%
“…The third example to be mentioned is the algorithm published by Theusinger et al [60,61]. This algorithm also takes into consideration different laboratory and POC results, such as ROTEM, CoaguCheck and Multiplate, and gives clear treatment orders.…”
Section: Algorithms Usedmentioning
confidence: 99%
“…All patients received intravenous single-dose antibiotic prophylaxis (cefazolin) 30 min prior to surgery. If necessary, allogeneic transfusion management and treatment of a potential traumaassociated coagulopathy during the hospital stay followed a fixed algorithm [18].…”
Section: Patientsmentioning
confidence: 99%